Wnt Signaling Is a Major Determinant of Neuroblastoma Cell Lineages - Szemes, Marianna; Greenhough, Alexander; Malik, Karim (Frontiers in Molecular Neuroscience, 2019)
The neural crest, which has been referred to as the fourth germ layer, comprises a multipotent cell population which will specify diverse cells and tissues, including craniofacial cartilage and bones, melanocytes, the adrenal medulla and the peripheral nervous system. These cell fates are known to be determined by gene regulatory networks (GRNs) acting at various stages of neural crest development, such as induction, specification, and migration. Although transcription factor hierarchies and some of their interplay with morphogenetic signalling pathways have been characterised, the full complexity of activities required for regulated development remains uncharted. Deregulation of these pathways may contribute to tumourigenesis, as in the case of neuroblastoma, a frequently lethal embryonic cancer thought to arise from the sympathoadrenal lineage of the neural crest. In this conceptual analysis, we utilise next generation sequencing data from neuroblastoma cells and tumours to evaluate the possible influences of Wnt signalling on neural crest GRNs and on neuroblastoma cell lineages. We provide evidence that Wnt signalling is a major determinant of regulatory networks that underlie mesenchymal/NCC-like cell identities through PRRX1 and YAP/TAZ transcription factors. Furthermore, Wnt may also co-operate with Hedgehog signalling in driving proneural differentiation programmes along the adrenergic lineage. We propose that elucidation of Signalling Regulatory Networks can augment and complement GRNs in characterising cell identities, which will in turn contribute to the design of improved therapeutics tailored to primary and relapsing neuroblastoma.